2020
DOI: 10.3389/fnins.2020.00232
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Associated Mutant Tau Prevents Circadian Changes in the Cytoskeleton of Central Pacemaker Neurons

Abstract: A hallmark feature of Alzheimer's disease (AD) and other Tauopathies, like Frontotemporal Dementia with Parkinsonism linked to chromosome 17 (FTDP-17), is the accumulation of neurofibrillary tangles composed of the microtubule-associated protein Tau. As in AD, symptoms of FTDP-17 include cognitive decline, neuronal degeneration, and disruptions of sleep patterns. However, mechanisms by which Tau may lead to these disturbances in sleep and activity patterns are unknown. To identify such mechanisms, we have gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…[ 23,26,41–44 ] The main role in this system is played by the SCN, which synchronizes the peripheral circadian clock network. [ 23,26,41,43,45,46 ] It has been demonstrated that SCN has a direct effect on the regulation of glucocorticoid circadian rhythms mediated by neural projections into the hypothalamic PVN. PVN, in turn, switches the light signal to the HPA axis, providing a basis for diurnal fluctuations in its activity with an increase in the concentration of circulating glucocorticoids during the active phase of the day (during the day in humans and primates and at night in nocturnal species).…”
Section: Responsivity Of the Hpa Axis To Stress Is Dependent On The Tmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23,26,41–44 ] The main role in this system is played by the SCN, which synchronizes the peripheral circadian clock network. [ 23,26,41,43,45,46 ] It has been demonstrated that SCN has a direct effect on the regulation of glucocorticoid circadian rhythms mediated by neural projections into the hypothalamic PVN. PVN, in turn, switches the light signal to the HPA axis, providing a basis for diurnal fluctuations in its activity with an increase in the concentration of circulating glucocorticoids during the active phase of the day (during the day in humans and primates and at night in nocturnal species).…”
Section: Responsivity Of the Hpa Axis To Stress Is Dependent On The Tmentioning
confidence: 99%
“…It is generally accepted that, with aging, a damping of the circadian amplitude of activity of SCN oscillatory neurons and of the HPA axis is observed. [ 20,22,40,41,46 ] The smoothing of the circadian rhythm of the SCN in the elderly correlates with neuronal degeneration in SCN and is often associated with earlier falling asleep and waking up. [ 20,26,41 ] The smoothing with aging of the circadian rhythm of HPA axis activity may be accompanied by an increase in the secretion of CORT in the evening and at night in humans and primates [ 20–22,25,35,40,47 ] and in rodents in the daytime.…”
Section: Responsivity Of the Hpa Axis To Stress Is Dependent On The Tmentioning
confidence: 99%
“…Sleep patterns in male and female CS and sniffer flies aged 1 week were assessed using the Drosophila Activity Monitoring Systems (DAMS) as described by Cassar et al [ 40 ] and Metaxakis et al [ 41 ]. For 7 days prior to placement in the monitors, CS flies were fed standard Drosophila food while sniffer flies were fed either standard Drosophila food or standard food supplemented with WS (0.5 mg/g or 2 mg/g).…”
Section: Methodsmentioning
confidence: 99%
“…The knock-in lines were created by replacing the dTau coding region with the cDNA for the human Tau 1N4R isoform using the CRISPR/Cas9 genomic editing system. A more detailed description is given in ( Cassar et al, 2020 ). These flies were originally in the w 1118 background but were backcrossed to CS to prevent phenotypes due to the w mutation.…”
Section: Methodsmentioning
confidence: 99%